ANALISIS DAMPAK KUALITAS KOMITE AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Mutmainnah,, Nurul; Wardhani, Ratna (UI Scholars Hub, 2013)
This research is aimed to examine the impact of audit committee quality measured by audit committee expertise, audit committee size, and number of meeting on the quality of company financial reporting with an audit quality as a moderating variable. This research uses three measures for financial reporting quality which are persistency, predictability, and conservatism. The results of this research show that audit committee quality affects financial reporting quality. Audit committee financial literacy significantly increase persistency and predictability of earnings. Size of audit committee positively affects earnings persistency and negatively affects earnings predictability and conservatism. Number of audit committee meeting also significantly increase persistency, predictability of earnings, and conservatism. We find a mixed evidence on the moderating role of audit quality in the the relationship between audit committee quality and financial reporting quality.